The Use of ChatGPT in Teaching Argumentative Text Writing: A Qualitative Study in an Indonesian Junior High School - Lisda Mamondol; Donal M. Ratu; Justien R.R. Wuisang (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This study aims to analyze the ability to write argumentative texts through the utilization of Artificial Intelligence (ChatGPT) in Indonesian language learning for ninth-grade students at SMP Advent 2 Manado. The research is based on the need for writing learning innovation in the digital era, particularly in helping students develop ideas, construct logical arguments, and improve written language skills. ChatGPT is used as a learning support medium to provide examples, guidance, and reinforcement in the argumentative text writing process. This study employs a descriptive qualitative approach with ninth-grade students as research subjects, while data were obtained through students' written work, learning observations, and documentation of student interactions with ChatGPT. The results show that the use of ChatGPT in Indonesian language learning helps students understand the structure of argumentative texts, develop ideas, and construct more systematic and coherent arguments. Students appeared more active and assisted in the process of writing argumentative texts, especially in formulating opinions and supporting reasons. Thus, ChatGPT can be utilized as an innovative alternative learning medium to improve students' argumentative text writing abilities, provided it is used in a directed manner with teacher guidance. Keywords: ChatGPT, Artificial Intelligence, argumentative text, writing ability, Indonesian language learning